2016
DOI: 10.1007/s00281-016-0571-3
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells in lung immunopathology

Abstract: Dendritic cells (DCs) lie at the heart of the innate immune system, specialised at recognising danger signals in many forms including foreign material, infection or tissue damage and initiating powerful adaptive immune and inflammatory responses. In barrier sites such as the lung, the instrumental role that DCs play at the interface between the environment and the host places them in a pivotal position in determining the severity of inflammatory disease. The past few years has seen a significant increase in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 175 publications
(200 reference statements)
0
54
0
1
Order By: Relevance
“…However, the potential mechanisms through which immune cells recognize fungal dysbiosis-derived signals to regulate distal allergic airway immune responses remain poorly characterized. We have recently shown that CX3CR1 + MNPs that express several antifungal receptors can efficiently recognize and uptake gut commensal fungi (Cook and MacDonald, 2016; Leonardi et al, 2018). Therefore, we next hypothesized that the direct sensing of fungi by gut CX3CR1 + MNPs might be responsible for the distal effects of fungal dysbiosis on systemic immunity and lung airway inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential mechanisms through which immune cells recognize fungal dysbiosis-derived signals to regulate distal allergic airway immune responses remain poorly characterized. We have recently shown that CX3CR1 + MNPs that express several antifungal receptors can efficiently recognize and uptake gut commensal fungi (Cook and MacDonald, 2016; Leonardi et al, 2018). Therefore, we next hypothesized that the direct sensing of fungi by gut CX3CR1 + MNPs might be responsible for the distal effects of fungal dysbiosis on systemic immunity and lung airway inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we next hypothesized that the direct sensing of fungi by gut CX3CR1 + MNPs might be responsible for the distal effects of fungal dysbiosis on systemic immunity and lung airway inflammation. Since CX3CR1 + MNPs are an abundant cell type in both the gut and the lung, we developed a strategy allowing us to efficiently deplete CX3CR1 + MNPs in the gut without affecting lung CX3CR1 + MNPs or other cell types previously shown to play a role in allergic airway inflammation (Cook and MacDonald, 2016; Gibbings et al, 2017; Mionnet et al, 2010; Tweedle and Deepe, 2018) (Figure S4A-C, and Figure 3A). Specifically, we used diphtheria toxin (DT) injected intraperitoneally (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…38 The biological activation and function of DCs depends on pattern recognition receptors (PRRs) such as C-type lectin receptors, toll-like receptors (TLRs) and Nod-like receptors, as well as by cytokine and chemokine receptors. 39 DCs can respond to a variety of external antigens of microbial and non-microbial origin (bacterial, viral, fungal, protozoa, allergens, etc.) as well as damage-associated molecule patterns.…”
Section: Dcsmentioning
confidence: 99%
“…Ultimately, the combination of PRRs and other stimulated receptors determines subsequent activation of DCs. 39 …”
Section: Dcsmentioning
confidence: 99%
“…For example, a microenvironment rich in IL-12 will lead to the activation and differentiation of natural killer (NK) lymphocytes. 22 It has recently been proposed that COPD may be an entity of autoimmune etiology, because autoantibodies have been found against peptides present in the extracellular matrix of lung tissue. Among them, the most important is elastin (anti-elastin antibodies are then formed).…”
Section: Adaptive Immunitymentioning
confidence: 99%